ACUTE AND SUBACUTE ANTI-INFLAMMATORY ACTIVITIES OF DICHLOROMETHANE EXTRACT OF CASSIA ALATA (LINN.) LEAVES IN WISTAR RATS - Da, F. L; Keugni, A. B; Belemtougri, G. R; Fotio, T. L. A; Dimo, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: In Burkina Faso, leaves of Cassia alata are used in the treatment of several diseases, including inflammation. This study evaluated the anti-inflammatory effects of the dichloromethane extract of Cassia alata leaves (CF-AECal) on different models of inflammation in wistar rats in order to enhance its use in traditional medicine. Materials and Methods: Acute inflammation was induced among rats with 0.1 ml of carrageenan, serotonin, histamine and dextrane 1%. The effects of the CF-AECal 50 mg/kg and 100 mg/kg were compared to the effects of diclofenal 5 mg/kg, prednisone 5 mg/kg, promethazine 1 mg/kg, cyproheptadin 2 mg/kg. Cotton pellet and air pouch - induced granuloma permitted to study CF-AECal effects on the subacute inflammation. The ways of administrations were intra peritoneal for the substances of inductions and oral for the molecules of references and CF-AECal. Result: Carrageenan-induced paw edema has been inhibited to 52.39% by CF-AECal 50 mg/kg and 50.17% by CF-AECal 100 mg/kg. Wet granulomas formation has been inhibited by CF-AECal 50 and 100 mg/kg to 20.94 and 57.82%. The dry granulomas were inhibited at 24.32 and 59.04% by CF-AECal 50 and 100 mg/kg. Air pouch fluid was significantly reduced by CF-AECal in comparison to the control group. There was a massive recruitment of leukocytes in the pocket granuloma of the control group. CF-AECal caused strong inhibition of this infiltration of leukocytes (p< 0.001). Conclusion: Dichloromethane extract of Cassia alata showed anti-inflammatory effects.